New data about semicircular canal morphology and locomotion in modern hominoids. Issue 1 (19th May 2017) - Le Maître, Anne; Schuetz, Philipp; Vignaud, Patrick; Brunet, Michel
Abstract: The labyrinth has two functional parts: the cochlea for audition and the vestibular system for equilibrioception. In the latter, the semicircular ducts and the otolithic organs are sensitive to rotational and linear accelerations of the head, respectively. The labyrinthine morphology influences perception accuracy, hence the adaptation to a specific locomotor pattern. The aim of this study is to determine the relationship between locomotion and semicircular canal morphology using geometric morphometrics, and to explain these links with existing functional models. The influence of factors other than functional constraints on labyrinthine morphology is discussed. The left bony labyrinth of 65 specimens was extracted virtually. Five extant hominoid species with various locomotion modes were sampled. A set of 13 landmarks was placed on the semicircular canals. After a Procrustes fit, their coordinates were analyzed using a principal component analysis. It was found that labyrinthine morphology is significantly distinct between species. More specifically, the differences involve a posterolateral projection of the lateral semicircular canal and the rotation of this canal relative to the vertical canals. This rotation occurs in the sagittal plane, which is consistent with previous studies based on traditional morphometrics. Among extant hominoids, the shape of the canals potentially discriminates species based on posture. This result could be used to reconstruct the locomotor pattern of fossil hominoids.